Enhancing the Effectiveness of Trichogramma Wasps through Innovative Formulations - Seyed Reza Fani (Journal of Biotropical Research and Nature Technology, 2025)
The mass of Trichogramma wasp larvae, recognized as a vital agent for pest biocontrol in Iran, is produced primarily in the form of Trichocards. These bacteria are utilized for the biocontrol of key and significant pests, such as rice stem borers, corn stem borers, apple worms, and pomegranate fruit worms. However, the application of this formulation presents several drawbacks, including the difficulty of installing cards across fields and orchards, the destruction of larvae by predatory insects, and the sensitivity of larvae to dryness and high temperatures, which can impair the effectiveness of the method. Alternative formulations such as capsules, balls, and liquids have been introduced in various countries to address these application issues. These alternatives offer advantages such as increased durability of larvae under adverse conditions, increased lifespan and efficiency of wasps, reduced production costs, faster operational speed, and greater willingness among farmers and orchardists to adopt biological methods. Given that the method of supplying Trichogramma larvae has remained unchanged in its production stages over the past 30 years in Iran, a continuous dynamic growth trend in the application of Trichogramma wasps will undoubtedly require a reassessment of various supply stages and an improvement in the production process.